Evaluasi Perbandingan Sistem Pembentukan Peraturan Perundang-undangan Indonesia–Madagaskar - Tolotsoa Fitahiana Ralaimbita; Safira Van Roselie B; Naurah Zakline Rasyah Amiseno (Fakultas Hukum, UPN Veteran Jawa Timur, 2025)
This paper analyzes the legislative regulation formation systems of Indonesia and Madagascar by examining how each country structures, develops, and enacts its formal legal norms. The problem underlying this study is the limited academic discussion comparing both systems, despite their shared civil law foundations and differing institutional arrangements. The main objective of this paper is to identify the similarities and differences in their legislative frameworks and to assess how these distinctions affect effectiveness, transparency, and public participation in the law-making process. This research uses a qualitative normative method supported by statutory analysis, constitutional documents, and recent scholarly sources. The study reviews Indonesia’s structured mechanism based on Undang-Undang Nomor 12 Tahun 2011 jo. UU 13/2022, which emphasizes planning instruments, hierarchical clarity, and shared legislative authority. It then contrasts this with Madagascar’s French-influenced system, where executive instruments such as ordonnances and décrets play a prominent role, and legislative planning is less formalized. The results show that Indonesia has a more detailed procedural framework and stronger participatory mechanisms, while Madagascar faces challenges related to institutional capacity and regulatory consistency. These findings suggest that both countries can benefit from mutual learning to strengthen transparency, improve coordination, and enhance the overall quality of legislative regulation. Keywords: Legislative Regulation Formation; Civil Law Systems; Indonesia; Madagascar; Comparaison; Regulatory Frameworks